PERANCANGAN PROMOSI GRUP MUSIK LALANG MELALUI VIDEO KLIP - HARDIAN TOMMY, Hendra Afriwan, S.Sn., M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Lalang is an indie folk band formed in padang with an exploration of local music of indonesia that contributed for the musics of indonesia. Lalang is an indie band that has it’s own characteristic where the lyric vocalize about nature and life. This things makes their character even stronger.The purpose of designing promotion lalang music group thought video clip to be expected that lalang would be more known in the public.Designed method of video clip is using descriptive qualitative method it means that the datas collected are not in the form of number, but the datas form an interviews ans documentation.This video clip is designed using visual communications of design theory, cinematography, audio visual, illustration, typography and colours. Datas collection was carried out using observation, interview and documentation methods. Data analysis method uses 5w+1h (why, when, where, why, who + how). Video clip design as the main media are also supported by another supporting medias, such as cd covers, posters, t-shirts, drumsticks, guitar picks, key chains and stickers. Which is useful as a supported of the main media and promotion.Keyword : Band, Indie, Folk, Lalang, dan Video Clip.